2003
DOI: 10.1159/000067707
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Kinase Type Tumor M2 in Urological Malignancies

Abstract: Introduction: The dimeric form of pyruvate kinase type M2 is overexpressed in tumor cells (TuM2-PK). The aim of the present study was to evaluate the clinical value of TuM2-PK as a tumor marker for renal cell carcinoma (RCC), transitional cell carcinoma of the bladder (TCC) and prostate cancer (PCA) by using a commercially available enzyme-linked immunosorbent assay for detection of TuM2-PK in plasma. Material and Methods: The TuM2-PK concentration in EDTA plasma was determined quantitatively and immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…The TuM2-PK concentration ranged from À37 U/ml to 285 U/ml in the tumour group and from À74 U/ml to 147 U/ml in the control group, respectively. This is consistent with previous studies reporting a mean interassay coefficient of variance ranging up to 17.5% and confirms the specific problems involved in the measurement of TuM2-PK (Varga et al, 2002;Hegele et al, 2003). Negative absorbance at low concentrations may probably be attributed to statistical spread as corroborated by the standard deviation (SD) of the standard concentrations of the test kits, or by hampering effects of particular serum components in some patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The TuM2-PK concentration ranged from À37 U/ml to 285 U/ml in the tumour group and from À74 U/ml to 147 U/ml in the control group, respectively. This is consistent with previous studies reporting a mean interassay coefficient of variance ranging up to 17.5% and confirms the specific problems involved in the measurement of TuM2-PK (Varga et al, 2002;Hegele et al, 2003). Negative absorbance at low concentrations may probably be attributed to statistical spread as corroborated by the standard deviation (SD) of the standard concentrations of the test kits, or by hampering effects of particular serum components in some patients.…”
Section: Discussionsupporting
confidence: 92%
“…The small tumour mass of OSCC, even in stage T4, could be a possible explanation for the findings of this study. However, the results are in agreement with Varga et al (2002), Hegele et al (2003), Oremek et al (2003b), Roigas et al (2003) and Staib et al (2006) who have found similar sensitivities and specificities for other malignancies and suggested that the TuM2-PK test was unsuitable for monitoring and early detection of cancer.…”
Section: Discussionsupporting
confidence: 90%
“…2001, Varga et al . 2002Hegele et al 2003). Based on our Tu M2-PK receiver operating characteristic (ROC) analysis results, and in consent with those studies, we do not suggest using this marker for primary diagnosis of RCC.…”
Section: Introductionmentioning
confidence: 66%
“…First and foremost, despite the increasingly appreciated role of PKM2 in oncogenesis in several non-BC types2223, the association of PKM2 with BC was only mentioned occasionally in the literature and not significantly beyond the conflicting results of whether plasma concentrations of PKM2 were diagnostic of urological malignancies2425. A rare exception was the attempt to determine, by mass spectrometry, the relative abundance of PKM2 versus its alternatively spliced isoform PKM126.…”
Section: Discussionmentioning
confidence: 99%